وديعة الأوراق المالية : دراسة قانونية مقارنة تتضمن في ثناياها دعوة المشرع العراقي الى إعادة النص على احكام وديعة الأوراق المالية الملغاة - د. ندى زهير الفيل (PROSPECTIVE RESEARCHES, 2023)
The current study tackles one of the most important bank operations related to shares and securities which is the financial operation deposit which has offer real several advantages to the bank and the client. The main purpose of this subject is to urge the Iraqi legislator to reconsider the text and act according to the legal rules relevant to this bank operation due to the developments and changes that the Iraqi financial and investment environment witnessed since the nineties decades of the last century represented by the companies law No. 21 for the year 1997 as well as the establishment of the Iraqi Market for bills. All these changes and developments constituted actual elements which encouraged the individuals to deal with the financial bills directing their savings and investments towards this kind of operation. As the overwhelming majority of these individuals are ignorant of how these bills are managed, they had to resort to the banks which have the technical experience in managing the portfolio and these banks can not manage these portfolios unless they hold contracts of the financial bills which constitute the legal framework of this operation.